Study of aggregating interval type-2 fuzzy model capabilities for forecasting of time series - Kondratenko, N. R.; Cheboraka, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper studies aggregating interval type-2 fuzzy model (AIT2FM) capabilities for forecasting of time series. This model consists of a set of interval type-2 fuzzy logic systems (IT2FLS) with various input numbers. IT2FLS is also studied to let us construct adequate IT2FLSs. It allows to construct adequate AIT2FM that gives narrower prediction intervals than IT2FLS.